Aboriginal Youth Gangs in Canada: (de)constructing an epidemic - Sinclair, Raven; Grekul, Jana (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2012)
The literature on gang activity in Canada indicates a proliferation of Aboriginal youth gangs, and the research tells us that child welfare involvement is a significant risk factor for gang participation. This article examines the child welfare and youth gang literature, and analyzes the complex interaction of structural factors facing Aboriginal youth in Canada in order to contextualize youth gang involvement within the larger system of social distress facing Aboriginal people. This paper scrutinizes the veracity of youth gang statistics and interrogates the Aboriginal youth gang discourse to discover that, although a problem clearly exists, the scope and substance of the situation in Canada needs to be more thoroughly researched in order to be accurately portrayed.